Sebaran Jenis Ikan Pelagis yang Ditangkap Menggunakan Pancing Ulur pada Rumpon di Laut Pemangkat Kabupaten Sambas - Heriyansah, Heriyansah; Saifullah, Saifullah (Nekton, 2023)
FAD technology has an indirect impact on the development of fishery stocks, thereby increasing the diversity of fish species in the FAD area. This study aimed to determine the types of pelagic fish caught using handlines around FADs. The target of this study was traditional fishermen. This research was conducted using survey methods and was directly involved in the fishing process. Fishing was carried out using handlines with specifications consisting of the main line, weight, swivel, fishing line, and hook. Fish catch samples were measured every week starting on the fourth week after the FADs were installed, with consideration of the regularity of the sample observation interval, the weather, and the fishermen's readiness. Data analysis was performed using tabulation, and the composition of the number and percentage of each type of catch was analyzed descriptively, which is presented in the form of a picture. The results showed that the types of fish caught were large trevally (Selaroides leptolepis) with an average catch of 10.1 kg/trip, mackerel (Rastrelliger sp.) with an average catch of 4.2 kg/trip, Kuwe (Caranx ignobillis) with an average catch of the average catch is 0.9 kg/trip and lastly the Tetengkek snakehead (Megalaspis cordyla).